PERANAN KEPALA DESA DALAM MEMBERDAYAKAN MASYARAKAT DI ERA OTONOMI DAERAH - Beni Wandagu (Master of Public Administration, Universitas Slamet Riyadi, 2015)
Beni Wandagau, 2015. Role of village head in community empowerment. Caseof empowering community of Karangturi Village Gondangrejo Sub DistrictKaranganyar Regency. Slamet Riyadi University, Thesis, unpublished.This research aimed to describe the role of village head in empowering thecommunity of Karangturi Village in Gondangrejo Sub District of KaranganyarRegency. The research method employed descriptive qualitative. thetechniques of collecting data used observation, interview and documentation.The sampling technique employed purposive sampling. Data validation wascarried out using data triangulation. The technique of analyzing data usedinteractive analysis model. Considering the result of research, the followingconclusions could be drawn. 1) The role of village head in communityempowerment included a) The role of village head in building constructionsector by reviving the mutual cooperation spirit among the members of society,and in religious activity by means of celebrating religious holiday andconducting monthly routine pengajian. The role of head village in buildingconstruction sector was also undertaken through village administrative buildingactivity, in which the village head routinely examine the village financialadministration in the objective of minimizing deviation and making the expenseconsistent with what specified in village budget and then reporting it to the BPD(Village Representative Assembly). Village economic sector development wasalso conducted by means of utilizing and managing the agricultural potential.The head village also gave the private the opportunity of developing thevillage’s potency in order to improve the village economy. b) The role of villagehead in coordinating development. The role of village head in coordinating thedevelopment, in which the village head always coordinated with the villageapparatus in conducting every activity. In addition to making coordination withhis/her subordinate, the village head always coordinated with his/her superiorlike camat (head of sub district) and local government. The head of villagealways invited the members of society to discuss either formally or informally.He/she did it to stimulate the villagers to participate actively in developmentprocess. The role of government, particularly head of village, was as thefacilitator of development. The head of village never discriminated his/herpeople. So that, no jealousy occurred among the members of society leading tosocial conflict. 2) The factors inhibiting the governmental organizationaldevelopment in Karangturi Village of Gondangrejo Sub District of KaranganyarRegency included: internal and external factors. The internal factor consisted ofhuman resource aspect in this case the poor quality and quantity of executiveapparatus, inadequate work infrastructure, low quality of human resource (theapparatuses of village government graduated from Senior High School only, onthe average), limited fund and the head of village’s attitude seeming to putothers’ interest superior to village development project. The external factorincluded the public participation in complying with the Village rule, and interstatusrelationship.Keywords: Village Head’s role, community empowerment building construction sectoreconomic sector development.